Constitutional recognition of rights and freedoms in France in the late nineteenth century - Bochkarev, Sergey (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The article deals with the ideological and theoretical foundations of the French constitutionalism of the Third Republic. The author notes that the Constitution of the Third Republic was a result of the continuous struggle between the supporters of the republican form of government and monarchists in the National Assembly. A compromise, reached by legislators in 1875, led to the uniting of different approaches to the organization of French governmental power in the Constitution. The views of Duke V. de Broglie, E. Laboulaye and L.-A. Prévost-Paradol were reflected in the Constitutional Law of the Third Republic. As a consequence, there was an acceptance of the institutions and authorities of public law specific to a dual monarchy. However, those public and legal institutions turned out to be indifferent to the form of government, that, in its turn, determined the longevity of the main constitutional and legal institutions, established in the last quarter of the nineteenth century.